The role of Syk signaling in antifungal innate immunity of human corneal epithelial cells - Liu, Ying (BMC Ophthalmol, 2015)
BACKGROUND: Fungal keratitis is a kind of intractable and sight-threatening diseases. Spleen-tyrosine kinase (Syk) is a non-receptor tyrosine kinase, which plays an important role in the signaling pathway of the receptors. In the current study, we investigate the expression and function of Syk in human corneal epithelial cells with Aspergillus fumigatus (A. fumigatus) infection. METHODS: Cultured telomerase-immortalized human corneal epithelial cells (THCEs) were treated with A. fumigatus hyphae with or without treatment of Syk inhibitors. Activation of Syk and the role of Syk in regulating inflammatory cytokines and chemokines expression were evaluated. The mRNA expression was determined by real time PCR, and protein activation was measured by western blotting. RESULTS: Syk protein was detected in THCEs, and its activation was enhanced after treatment of A. fumigatus hyphae. Expression of inflammatory cytokines (IL-1β and IL-6) and chemokines (IL-8 and CXCL1) mRNA were significantly increased after stimulation of A. fumigatus hyphae in THCEs. Activation of Syk and expression of IL-1β, IL-6, IL-8 and CXCL1 by A. fumigatus hyphae were blocked by Syk inhibitors. CONCLUSION: These findings demonstrate that normal human corneal epithelial cells produce Syk, and Syk activation plays an important role in regulating A. fumigatus hyphae-induced inflammatory responses in THCEs.